2021
DOI: 10.25122/jml-2021-0270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the antibacterial effect of cobalt nanoparticles against multi-drug resistant pathogens

Abstract: This study aimed to estimate the effect of cobalt nanoparticles (Co NPs) with different concentrations against multidrug-resistant (MDR) pathogenic bacteria. Three isolates of (gram-positive), . (gram-negative), and (gram-negative) bacteria were extracted from various clinical examples utilizing routine methods on bacteriological culture media. The antibacterial sensitivity of commercial antibiotics such as Ciprofloxacin, Cefotaxime, Gentamycin, and Amoxicillin was broken down on a Muller Hinton agar plate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…27 In addition, it has low toxicity, as demonstrated by L. Qian et al 14 It is important to highlight that several mechanisms of antimicrobial action have been associated with the release of Co 2+ ions, such as the change in the correction functions of plasma membrane proteins and accumulation in the cell wall, leading to a decrease in its permeability. 10,48 Concerning composites, Qian et al synthesized new ZIF-67 and cellulose-based composites with outstanding mechanical properties and antibacterial activity against E. coli. 14 Recently, Tao et al obtained a composite consisting of osteogenic growth peptide (OGP) loaded zeolitic imidazolate framework-67 (ZIF-67) and coated it on titanium dioxide nanotubes (TNTs) (TNT-ZIF-67@OGP) with strong antibacterial activity against E. coli, S. aureus, Streptococcus mutans (S. mutans), and methicillin-resistant Staphylococcus aureus (MRSA).…”
Section: Resultsmentioning
confidence: 99%
“…27 In addition, it has low toxicity, as demonstrated by L. Qian et al 14 It is important to highlight that several mechanisms of antimicrobial action have been associated with the release of Co 2+ ions, such as the change in the correction functions of plasma membrane proteins and accumulation in the cell wall, leading to a decrease in its permeability. 10,48 Concerning composites, Qian et al synthesized new ZIF-67 and cellulose-based composites with outstanding mechanical properties and antibacterial activity against E. coli. 14 Recently, Tao et al obtained a composite consisting of osteogenic growth peptide (OGP) loaded zeolitic imidazolate framework-67 (ZIF-67) and coated it on titanium dioxide nanotubes (TNTs) (TNT-ZIF-67@OGP) with strong antibacterial activity against E. coli, S. aureus, Streptococcus mutans (S. mutans), and methicillin-resistant Staphylococcus aureus (MRSA).…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with the previous studies in which higher concentrations of ZnO-NPs showed stronger antimicrobial effects [8] , [25] , [26] . However, some studies showed that the inhibition zone of nanoparticles starts to shrink beyond an optimal concentration [28] , [29] . One of the possible reasons may be due to the accumulation of nanoparticles in high concentrations and the inability to penetrate into bacterial cells [28] , [29] .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies showed that the inhibition zone of nanoparticles starts to shrink beyond an optimal concentration [28] , [29] . One of the possible reasons may be due to the accumulation of nanoparticles in high concentrations and the inability to penetrate into bacterial cells [28] , [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Cobalt ion has mild toxicity for a healthy individual, but a cobalt complex has been used as an anticancer agent . Meanwhile, recent studies reveal that cobalt nanoparticles , and cobalt-related materials have antibacterial properties. However, the traditional method for the synthesis of cobalt nanowires required high temperatures and many reaction steps. Therefore, developing a simple technique to synthesize the cobalt-related nanowires at room temperature is essential to produce an efficient antibacterial material.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt ion has mild toxicity for a healthy individual, 14 but a cobalt complex has been used as an anticancer agent. 15 Meanwhile, recent studies reveal that cobalt nanoparticles 16,17 and cobalt-related materials 18 have antibacterial properties. However, the traditional method for the synthesis of cobalt nanowires required high temperatures and many reaction steps.…”
Section: ■ Introductionmentioning
confidence: 99%